Functional magnetic resonance imaging - Huettel, Scott A; Song, Allen W; McCarthy, Gregory (Sinauer Associates, 2004)
This textbook provides a true introduction to functional magnetic resonance imaging (fMRI), which has become the dominant research technique in cognitive neuroscience. Although there is extraordinary interest in fMRI among researchers, instructors, and students alike, its instruction has faced a set of challenges. Existing texts are targeted toward practicing scientists in the field, and assume a level of expertise not possessed by most students. Furthermore, most students do not have access to fMRI equipment and data, so they have no opportunity to gain hands-on experience. This textbook overcomes these limitations by presenting a comprehensive overview of all aspects of fMRI, designed with undergraduate students, graduate students, and beginning researchers in mind. The book progresses through 15 chapters. It begins with an introduction to fMRI and its history, principles, and technical requirements. The following several chapters cover the physics of fMRI, with careful attention devoted toward relating abstract concepts to research applications. Subsequent chapters cover the basic biological properties of the fMRI signal, including its spatial and temporal properties and its variability. Systematic discussions of research design and experimental analysis are included, and will be of particular interest to the many students with graduate or medical school aspirations. The book ends with discussions of future directions for fMRI, not only in terms of advances in understanding the brain and methodological improvements, but also in the integration of fMRI with other research techniques. Included with every copy of the book is a comprehensive CD-ROM containing study questions for each chapter of the book, suggested lab exercises, fMRI data sets including both functional and anatomical data, a tools section, and compete glossary. The authors\' goal was to create a book that is sufficiently scientifically rigorous for researchers in the field, but also accessible enough to be easily read and understood by beginning students. All chapters are copiously illustrated, with key terms described in a marginal glossary, and have annotated lists of references. The book can be used as the primary text for classes in fMRI, or as a secondary text for cognitive neuroscience, research methods, or other courses.
Keywords: neurovědy; neurologie; radiologie, nukleární medicína a zobrazovací metody